A magnetic self-contained thermochromic system with convenient temperature range12. Issue 6 (25th February 2019) - Billeci, Floriana; Gunaratne, H. Q. Nimal; D'Anna, Francesca; Morgan, Grace G.; Seddon, Kenneth R.; Plechkova, Natalia V.
Abstract : A sugar-based ionic liquid ligand coordinated to cobalt(ii ) exhibits magnetic switching and marked thermochromism in spectator ionic liquid solution/polymer films over a convenient temperature range (20–60 °C), resulting in a potential energy storage system. Abstract : A new ionic liquid with sugar-based ligand has been prepared and used to coordinate cobalt(ii ), at low loading, in an ionic liquid solution. The system obtained reveals magnetic switching and marked thermochromism in solution/polymer films over a convenient temperature range (20–60 °C). This system is self-contained, devoid of any volatile substances, and reproducible over multiple thermal cycles. The colour change can be attributed to a change in the coordination geometry from octahedral (pink) at room temperature to tetrahedral (blue) on warming, monitored by 59 Co NMR spectroscopy, which was used for the first time to study the change. This material may find applications in stimuli -responsive smart systems aimed at energy storage applications.